AN ANALYSIS OF STUDENTS’ SPEAKING ABILITY OF PROCEDURE TEXT AT GRADE X OF SMK NEGERI 1 AIR JOMAN IN ACADEMIC YEAR OF 2020/2021 - Hamidah Sidabalok , (Universitas Asahan, 2021)
ABSTRACTThis research purposed to measure the students’ ability procedure text in speakingprocedure text. The location of this research was SMK 1 Airjoman. The time that wasalocated in this research was one month. This research was conducted in descriptivequantitative. The method in taking the sample was random sampling. The population ofthis research was all of grade X students that consisted of two classes. Each class wasconsisted of 39 students for 1 class and 30 students for one class with the total populationwas 80 students. Because of this research was using descriptive quantitative, the researcherchoose X TPL and XTKR with 20 students as the sample of the research. The instruments thatused in this research was a test. The test was a multiple choice test. The test was askingthe students to rearrange the procedure text to a good text. Based on the result of theresearch, the students’ ability in speaking procedure text was low. It was proved by theirmean score in speaking procedure text that only reach 59.0. This indicated that thecalculated value of r is greater than the critical value at the level 5% = 0.312 and at levell1% = 0.403. [0.81>0.312]. It can be conluded that there is any significant an analysis ofstudents speaking ability of procedure text significantly. From this research, there are threeinstruments in examining their ability including pronunciation, fluency, and intonation.Pronunciation and Intonation were the most troublesome for the students because thestudents mostly made mistakes in that parts. It is hoped that by the finding of these trouble,there will be future research on this subject so that there will be some method or strategythat enable to overcome these troubles.